UFASOMES: UNSATURATED FATTY ACID BASED VESICULAR DRUG DELIVERY SYSTEM - ARUNDHASREE; R., RAJALAKSHMI; R., AISWARYA; KUMAR, ABHIRAMI RAJENDRA; KUMAR, SREELAKSHMI S.; NAIR, SREEJA C. (International Journal of Applied Pharmaceutics, 2021)
Various novel drug delivery systems have been developed encompassing several administration routes to deliver drugs at a rate decided as per the need of the body during the course of treatment and to achieve targeted therapy, also decreases undesirable side effects. Different types of vesicular drug delivery systems were developed, such as liposomes, niosomes, ufasomes etc. Ufasomes are unsaturated fatty acid vesicles which is a suspension of closed lipid bilayer formed from fatty acid and their ionized species having limited, narrow pH ranging from 7-9. Composition of fatty acid molecules is such that the hydrocarbon tails are pointed towards the inner core of the membrane and the carboxyl group are in touch with water. Stable ufasomes preparation mainly relies on appropriate choice of fatty acid, cholesterol quantity, range of the pH, buffer and lipoxygenase amount. Recent innovation provides very efficient features such as stability considerations, dynamic features and microscopic features of ufasomes. The article furthermore provides the difference between ufasomes with liposomes. For this review, the complete databases have been collected from various search engines such as researchgate, elsevier, pubmed, sciencedirect, google scholar, scopus etc., from the year 1965-2020 using the following keywords.